Framing Oleh NGO Terkait Pelaksanaan Bahrain Grand Prix Sebagai Alat Sportswashing Pemerintah Bahrain Terhadap Isu Pelanggaran HAM Tahun 2011-2020 - Patty, Angie Marsha; Priadarsini, Ni Wayan Rainy; Dewi, Putu Ratih Kumala (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2023)
Human rights violations in Bahrain since the Arab Spring have continued and are getting worse. This is a concern for the international public, including Non-governmental Organizations (NGOs) working on humanitarian issues as well as various media that assist in raising issues, both domestically and internationally. Responding to this, the response from the Government of Bahrain is considered slow, coupled with the implementation of the Bahrain Grand Prix in the midst of human rights violations. The public also demanded real action and accountability from the Government of Bahrain through protests that ended in chaos due to the involvement of various parties. The issue of human rights violations has been limited by the Bahraini government through repressive measures, such as arresting and detaining activists and restricting access to the media. The Bahraini government's action was framed as a form of sports washing to cover up the issue of human rights violations that occurred. To help advocate for these issues, activists, media, and NGOs framed the Bahrain Grand Prix in 2011-2020 to raise the issue of human rights violations that occurred in Bahrain and form an alliance through the establishment of a transnational advocacy network as an effort to pressure the Bahraini government.